2009
DOI: 10.1021/ie9012437
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Methylene Blue Dye Using Ultraviolet Light Emitting Diodes

Abstract: This study was focused on the application of ultraviolet light emitting diodes (UV-LED) as an alternate source for the photocatalytic degradation of methylene blue (MB), which was used as a model compound. A simple reactor arrangement was made to carry out the photocatalytic degradation of methylene blue dye. The photocatalytic activity of P-25 Degussa TiO 2 was evaluated using UV-LED reactor. The decomposition of MB dye in aqueous solution by TiO 2 photocatalytic process with the UV-LED was found to be techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(135 citation statements)
references
References 39 publications
7
126
0
2
Order By: Relevance
“…The reduction in the degradation efficiency aer 10 catalytic cycles, can be explained by the material loss during the recovering procedure because of the difficulty to avoid any loss of catalyst materials during the washing and ltration process. [32][33][34][35] Aer ten cycles of reusability test, TiO 2 NPs were analysed using XRD and FESEM to determine its phase, porosity and morphology stability. Fig.…”
Section: Xps Analysismentioning
confidence: 99%
“…The reduction in the degradation efficiency aer 10 catalytic cycles, can be explained by the material loss during the recovering procedure because of the difficulty to avoid any loss of catalyst materials during the washing and ltration process. [32][33][34][35] Aer ten cycles of reusability test, TiO 2 NPs were analysed using XRD and FESEM to determine its phase, porosity and morphology stability. Fig.…”
Section: Xps Analysismentioning
confidence: 99%
“…We are with the opinion that this effect is resulting in the changing relation of the continuous delivery of oxidation radicals from the irradiated nanotubes with the continuously lowered concentration of oxidizable methylene-blue molecules. In comparison of other work using TiO 2 /methylene-blue degradation systems based on nanoparticles [1,34] minimum of 50% shorter degradation time, using a lower irradiation power with a consideration on the used dye concentration.…”
Section: Photocatalytic Activitymentioning
confidence: 92%
“…Yao et al observed that the photodegradation efficiency decreases in the order of pH 2 > pH 9 > pH 7 and got best results for photodecradation at pH 2 [34]. Based on literature reports, best results for photocatalytic degradation of methylene-blue have been shown with dye concentrations of about 3.12 × 10 −5 mol/l in reference to a photocatalyst concentration of around 1 g/l [1]. Due to the low weight of the TNTs and by keeping reference to literature results vis-a-vis the achieved results of this report -a dye concentration of 1.3 × 10 −5 mol/l and five polycarbonate templates containing the TNTs were used for each photocatalytic dye degradation sample.…”
Section: Photocatalytic Activity Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these species, hydroxyl radicals (·OH) have been reported to be a key to the decomposition of organic compounds due to their high reactivity [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%